Re-stricture after buccal mucosal graft urethroplasty: a systematic review and meta-analysis - Gustavo Bono Yoshikawa; Gabriella Giandotti Gomar; Giovanna Ceccatto Gadens; Beatriz França Zanetti Saes; Maria Eduarda Andrade Galiciolli; Meire Ellen Pereira; Quelen Iane Garlet; Cláudia Sirlene Oliveira (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: To determine risk factors for re-stricture after buccal mucosal graft urethroplasty (BMGU) through a systematic review and meta-analysis. Methods: Following PRISMA guidelines, we collected data from PubMed, Scientific Electronic Library Online (SciELO), and Web of Science databases. The eligibility criteria included studies with male patients over 18 years old with urethral stricture recurrence after BMGU. Results: We retrieved 646 papers from three electronic databases. Records that did not meet the eligibility criteria and duplicates were excluded, resulting in 14 papers (3,240 patients) that underwent qualitative analysis, from which nine papers were suitable for meta-analysis. The meta-analysis identified diabetes mellitus (relative risk – RR: 1.58 [95% confidence interval – 95%CI 1.02–2.46];p = 0.04), penile/peno-bulbar site (RR: 1.57 [95%CI 1.04–2.37]; p = 0.03), and stricture size higher than 7 cm (RR: 4.13 [95%CI 2.42–7.04]; p 0.00001) as a predictive factor of re-stricture. Conclusions: These findings may improve understanding the risk factors for this type of urethroplasty and help surgical decisions. For a more effective analysis, larger and better-distributed study groups and cohorts are needed in the future to clarify whether the combination of a previous disease and the urethroplasty etiology may impact a recurrence-free outcome after stricture correction.